Creativity as a mediator between personal accomplishment and task performance: A multigroup analysis based on gender during the COVID-19 pandemic - Karaboga, Tugba; Erdal, Nurgul; Karaboga, Hasan Aykut; Tatoglu, Ekrem (SPRINGER, 2023)
The current pandemic of coronavirus disease 2019 (COVID-19) is not only a health crisis but also a social crisis that affects all people and all parts of society from various perspectives. Effective management of the emotional and psychosocial effects of the pandemic is a critical issue for individuals and societies. In this study, the mediating role of creativity on the relationship between personal accomplishment and task performance was examined during the COVID-19 pandemic. In addition, a gender-based comparison analysis was performed to extend the analysis results. Survey-based research data were collected from 322 people working in different sectors. Partial least squares-based structural equation modeling (PLS-SEM) was used to analyze research data. The results indicated that personal accomplishment had a significant positive effect on both creativity and task performance. Also, it was found that creativity had a mediating role in the relationship between personal accomplishment and task performance. Lastly, the gender-based multigroup analysis (MGA) revealed a significant difference between male and female participants with respect to the relationship between personal accomplishment and task performance, between creativity and task performance, between personal accomplishment and task performance through creativity.
Keywords: COVID-19; Personal accomplishment; Creativity; Task performance; Self-efficacy theory; PARTIAL LEAST-SQUARES; SELF-EFFICACY; EMPLOYEE CREATIVITY; PLS-SEM; BURNOUT; ORGANIZATIONS; PREDICTORS; INNOVATION; VALIDITY; CONTEXT; Psychology